New species of Pandanus (Pandanaceae) from Kabaena Island, South East Sulawesi, Indonesia - Keim, Ary PRIHARDHYANTO (REINWARDTIA, 2009)
Pandanus kabaenaensis A.P. Keim is described as a new species from Kabaena Island in the Province of South East Sulawesi, Indonesia.